Enhanced nitric oxide generation mitigates cadmium toxicity via superoxide scavenging leading to the formation of peroxynitrite in barley root tip - Demecsová, Loriana (Journal of plant physiology, 2019)
Copyright © 2019 Elsevier GmbH. All rights reserved.